Patologi Humanisme (Modern): Dari Krisis Menuju 'Kematian' Epsitemologi Rasional - Listiyono Santoso (Jurnal Filsafat "WISDOM", 2003)
The Great project of modernism epistemologically is built of Cartesian rationalism foundation. In teh one hand, it gives positive contribution in civilization development, but in the other hand, it conceives dehumanization. Cartesian's rational epistemology which influnced the isms in philosophy, in reality it creates the degradation of human values